Examining the Connection Between Missing Persons and Victimization: An Application of Lifestyle Exposure Theory. (March 2023) - Ferguson, Lorna; Elliott, Melissa; Kim, Sin
Victimization has been anecdotally connected to missing persons within several reviews, inquiries, and media stories, particularly in consequence of missing-turned-serial murder cases. However, this has been paid little attention within the scholarship. To remedy this gap, this study empirically explores the link between missing persons and victimization through the perspective of lifestyle exposure theory. A qualitative thematic analysis of 1, 920 missing person files uncovers several demographic and lifestyle factors implicating victimization risk, as well as their ranked aggregated and disaggregated saliency. Examples include criminality, victimizing events, sex work, and gender identity. Also discovered is that the context and nature of victimization risk differ for specific people and groups. The implications of these findings and future research areas are herein discussed.